Quality of life and related factors among chronic hepatitis B-infected patients: a multi-center study, Turkey. Issue 1 (December 2016) - Karacaer, Zehra; Cakir, Banu; Erdem, Hakan; Ugurlu, Kenan; Durmus, Gul; Ince, Nevin; Ozturk, Cinar; Hasbun, Rodrigo; Batirel, Ayse; Yilmaz, Esmeray; Bozkurt, Ilkay; Sunbul, Mustafa; et al.
Abstract Background The aim of this study was to assess health-related quality of life (HRQOL) among chronic hepatitis B (CHB) patients in Turkey and to study related factors. Methods This multicenter study was carried out between January 01 and April 15, 2015 in Turkey in 57 centers. Adults were enrolled and studied in three groups. Group 1: Inactive HBsAg carriers, Group 2: CHB patients receiving antiviral therapy, Group 3: CHB patients who were neither receiving antiviral therapy nor were inactive HBsAg carriers. Study data was collected by face-to-face interviews using a standardized questionnaire, Short Form-36 (SF-36) and Hepatitis B Quality of Life (HBQOL). Values equivalent top  < 0.05 in analyses were accepted as statistically significant. Results Four thousand two hundred fifty-seven patients with CHB were included in the study. Two thousand five hundred fifty-nine (60.1 %) of the patients were males. Groups 1, 2 and 3, consisted of 1529 (35.9 %), 1721 (40.4 %) and 1007 (23.7 %) patients, respectively. The highest value of HRQOL was found in inactive HBsAg carriers. We found that total HBQOL score increased when antiviral treatment was used. However, HRQOL of CHB patients varied according to their socio-demographic properties. Regarding total HBQOL score, a higher significant level of HRQOL was determined in inactive HBV patients when matched controls with the associated factors were provided. Conclusions The HRQOL score of CHB patients was higher than expected and it can be worsen when the disease becomes active. Use of an antiviral therapy can contribute to increasing HRQOL of patients.